Molecular detection of Paracoccidioides brasiliensis in soil - Theodoro, R. C.; Candeias, JMG; Araujo, J. P.; Bosco, SDG; Macoris, SAD; Padula, L. O.; Franco, M.; Bagagli, E. (Taylor & Francis Ltd, 2005)
The objective of the present study was to evaluate different techniques for the detection of Paracoccidioides brasiliensis in soil, e.g., culture, animal inoculation and specific DNA amplification by Nested PCR. We designed species-specific inner primers derived from rDNA regions (ITS, 5.8S gene) and found their sensitivity to be higher than culture and animal inoculation. In addition, the sensitivity of these primers was higher than p27-gene primers developed for detection of P brasiliensis in soil in a previous study. DNA from P brasiliensis was detected in soil artificially seeded with the fungus (positive soil control) and from environmental samples collected in an armadillo burrow.
Keywords: detection; Paracoccidioides brasiliensis; PCR; soil